NMR Assignment of Methyl Groups in Immobilized Proteins Using Multiple-Bond 13C Homonuclear Transfers, Proton Detection, and Very Fast MAS - Paluch, Piotr; Augustyniak, Rafal; Org, Mai-Liis; Vanatalu, Kalju; Kaldma, Ats; Samoson, Ago; Stanek, Jan (Frontiers in Molecular Biosciences, 2022)
In Nuclear Magnetic Resonance spectroscopy of proteins methyl protons play a particular role as extremely sensitive reporters on protein dynamics, allosteric effects and protein-protein interactions, accessible even in large molecular weight systems. The notorious issue of their chemical shift assignment is addressed here by a joint use of solid-state 1H-detected methods at very fast (nearly 100 kHz) magic-angle spinning, partial deuteration and high-magnetic fields. The suitability of a series of RF schemes is evaluated for the efficient coherence transfer across entire 13C side-chains of methyl-containing residues, which is key for establishing connection between methyl and backbone 1H resonances. Performance of ten methods for recoupling of either isotropic 13C-13C scalar or anisotropic dipolar interactions (five variants of TOBSY, FLOPSY, DIPSI, WALTZ, RFDR and DREAM) is evaluated experimentally at two state-of-the-art spinning (55 and 94.5 kHz) and static magnetic field conditions (18.8 and 23.5 T). Model isotopically-labelled compounds (alanine and Met-Leu-Phe tripeptide) and ILV-methyl and amide-selectively protonated, and otherwise deuterated chicken alpha-spectrin SH3 protein are used as convenient reference systems. Spin dynamics simulations in SIMPSON are performed to determine optimal parameters of these RF schemes, up to yet experimentally unavailable spinning frequencies (200 kHz) and B0 field strengths (30.5 T). The concept of linearization of 13C side-chain by appropriate isotope labelling is revisited and showed to significantly increase sensitivity of methyl-to-backbone correlations. A resolution enhancement provided by 4D spectroscopy with non-uniform (sparse) sampling is demonstrated to remove ambiguities in simultaneous resonance assignment of methyl proton and carbon chemical shifts.